2017
DOI: 10.23970/ahrqepccer199
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for Basal Cell and Squamous Cell Carcinoma of the Skin

Abstract: Key MessagesPurpose of Review Assess comparative effectiveness and safety of treatments for basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). Key Messages• Comparative evidence on treatment of BCC and SCC is limited. Many comparisons were evaluated in one or two randomized controlled trials only.• Surgery and radiotherapy have lower recurrence rates for BCC than interventions that destroy lesions with heat or cold, photodynamic therapy (PDT), or curettage.• There is moderate confidence that PDT for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…Surgical excision is often regarded as the standard treatment for high-risk BCC and is also used in the treatment of low-risk BCC, as it offers the lowest recurrence rates [ 97 , 139 , 140 ]. However, PDT and other noninvasive treatments are also appropriate for low-risk BCC of superficial depth, with a particular advantage for multiple and large surface area lesions or poorly healing skin sites, and a cosmetic outcome is demonstrably superior with PDT [ 91 , 92 , 93 ] A recent systematic review and network meta-analysis indicated that, while there was a clear advantage of lower recurrence rates of surgery over PDT, there was a moderate strength conclusion that PDT was associated with significantly better cosmetic outcomes than surgery [ 141 , 142 ].…”
Section: Outcomes Of Topical Pdt Treatment Of Bccmentioning
confidence: 99%
“…Surgical excision is often regarded as the standard treatment for high-risk BCC and is also used in the treatment of low-risk BCC, as it offers the lowest recurrence rates [ 97 , 139 , 140 ]. However, PDT and other noninvasive treatments are also appropriate for low-risk BCC of superficial depth, with a particular advantage for multiple and large surface area lesions or poorly healing skin sites, and a cosmetic outcome is demonstrably superior with PDT [ 91 , 92 , 93 ] A recent systematic review and network meta-analysis indicated that, while there was a clear advantage of lower recurrence rates of surgery over PDT, there was a moderate strength conclusion that PDT was associated with significantly better cosmetic outcomes than surgery [ 141 , 142 ].…”
Section: Outcomes Of Topical Pdt Treatment Of Bccmentioning
confidence: 99%
“…Although the current treatments are effective to varying degrees, they tend to lack specificity and often do not target the tumor itself or the environment in which it exists ( 6 ). They are also associated with a high incidence of adverse effects and yield undesirable cosmetic results ( 7 , 8 ). As such, alternative treatments options for patients with these conditions are needed.…”
Section: Introductionmentioning
confidence: 99%
“…В доступной литературе широко обсуждаются проблемы лечения пациентов пожилого и старческого возраста со злокачественными новообразованиями кожи [1]. Это связано с трудностями использования специальных методов терапии, которые могут негативно отразиться на качестве жизни больных [2][3][4][5]. Решение о проведении противоопухолевой терапии у долгожителей (лиц старше 90 лет) требует большого профессионализма от клиницистов.…”
Section: Introductionunclassified